Challenges in Financing Education, Health, and Social Protection Expenditures in Zimbabwe - World Bank (Washington, DC, 2014)
The Government of Zimbabwe (GOZ) faces difficult choices in managing the size of its civil service wage bill. The Government understands the need to watch the escalating wage bill carefully and put in place a strategy to steer it to a sustainable level as early as possible. Historical and international comparisons suggest that an overall wage bill of around 10 percent of GDP should be the medium-term target. This note illustrates that Zimbabwe could take immediate steps in 2010 and 2011 that will put it on the path of a sustainable level of wage bill in the medium-term. The focus of efforts to contain the wage bill should be on short-term measures because designing and implementing a medium-term approach to wage bill management would be too challenging in view of prevailing economic uncertainty and complex political reality. The note covers the staff employed by the Central Government, including uniformed services and staff employed by the Grant-in-Aided (GIA) institutions. The staff employed by local governments and public enterprises are excluded because direct transfers from the central budget to local government and public enterprises are rather small. (annex A has an outline of the institutional aspects of civil service in Zimbabwe). Given the paucity of information, the note does not make any recommendations specific to the GIA wage bill.